1964
DOI: 10.1002/hlca.19640470317
|View full text |Cite
|
Sign up to set email alerts
|

Massenspektrometrie und ihre Anwendung auf Strukturelle und stereochemische Probleme. LII. Vinca‐Alkaloide, 28. Mitteilung. Über die Struktur und massenspektrometrische Fragmentierung von Vindolinin

Abstract: Vinca-Alkaloide, 28. Mitteilung [2] Vor kurzem [3] wurde von uns fur das Vinca-Alkaloid Vindolinin [4] [5] die Strukt u r I oder I1 vorgeschlagen. Solchen Strukturen kommt ein bedeutendes biogenetisches Interesse zu, liegt doch damit erstmals ein Alkaloid mit Aspidospermin-ahnlichem Gerust vor, das nicht aus der Gattung As$idosperma isoliert wurde. Inzwischen sind weitere Reispiele fur das Vorkommen Aspidospermin-artiger Strukturen in verschiedenen Apocynaceae-Arten bekannt geworden [6]. Unser Strukturvorschla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1964
1964
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The densely functionalized, 2,3-indoline-fused tetracyclic structure of 6 coupled with its ready access provides an excellent starting point for synthesis of indoline-containing alkaloids. As a preliminary exploration of its synthetic application, Scheme illustrates a short synthesis of the tetracyclic core of vindolinine (i.e., pyrrolidine 12 ) …”
mentioning
confidence: 99%
“…The densely functionalized, 2,3-indoline-fused tetracyclic structure of 6 coupled with its ready access provides an excellent starting point for synthesis of indoline-containing alkaloids. As a preliminary exploration of its synthetic application, Scheme illustrates a short synthesis of the tetracyclic core of vindolinine (i.e., pyrrolidine 12 ) …”
mentioning
confidence: 99%
“…This was one of the first examples in indole alkaloid chemistry where the total structure of a novel alkaloid was deduced primarily from these measurements. Subsequently, chemical evidence was presented (3) showing that C-10 possessed two hydrogen atoms and it was concluded that Structure II was the correct representation for vindolinine.…”
mentioning
confidence: 99%